EDUKASI DAN BIMBINGAN TEKNIS HOME PROGRAM HIDROTERAPI PADA ORANG TUA DAN PENDAMPING ANAK BERKEBUTUHAN KHUSUS - Trisnowiyanto, Bambang; Andriani, Isna (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2024)
Children with special needs or disabilities, especially physical dysfunction, require physical therapy to stimulate growth and development throughout their life cycle. Parents and/or caregivers who accompany children with special needs 24 hours a day have a primary role in improving physical functional abilities and achieving children's independence in daily activities. Community service was expected to empower parents and/or caregivers accompanying children with special needs to apply a home hydrotherapy program. Empowerment in the community of parents with children with special needs is carried out using educational methods using power point media and guidance on home hydrotherapy program techniques through direct practical application. Community service activities were carried out in Padang City, which were attended by 130 parents with children with special needs spread across West Sumatra Province. The level of knowledge and skills of parents and/or companions of children with special needs regarding the application of home hydrotherapy programs has increased. Educational activities and guidance on home hydrotherapy program techniques for parents of children with special needs have a positive impact in helping to improve functional abilities and achieve children's independence in daily activities.